Impact of Phage CDHS-1 on the Transcription, Physiology and Pathogenicity of a Clostridioides difficile Ribotype 027 Strain, R20291 - Janet Y. Nale (MDPI AG, 2021)
All known Clostridioides difficile phages encode integrases rendering them potentially able to lyse or lysogenise bacterial strains. Here, we observed the infection of the siphovirus, CDHS-1 on a ribotype 027 strain, R20291 and determined the phage and bacterial gene expression profiles, and impacts of phage infection on bacterial physiology and pathogenicity. Using RNA-seq and RT-qPCR we analysed transcriptomic changes during early, mid-log and late phases of phage replication at an MOI of 10. The phage has a 20 min latent period, takes 80 min to lyse cells and a burst size of ~37. All phage genes are highly expressed during at least one time point. The Cro/C1-transcriptional regulator, ssDNA binding protein and helicase are expressed early, the holin is expressed during the mid-log phase and structural proteins are expressed from mid-log to late phase. Most bacterial genes, particularly the metabolism and toxin production/regulatory genes, were downregulated from early phage replication. Phage-resistant strains and lysogens showed reduced virulence during Galleria mellonella colonization as ascertained by the larval survival and expression of growth (10), reproduction (2) and infection (2) marker genes. These data suggest that phage infection both reduces colonization and negatively impacts bacterial pathogenicity, providing encouraging data to support the development of this phage for therapy to treat C. difficile infection.